Distribution of extensively drug-resistant Gram-negative bacteria, their antibiotic susceptibility profile, and the detection of metallo-β-lactamase production by them from a tertiary care center in New Delhi, India - Sarjana Shuchi; Shweta Satija; Manoj B Jais (Asian Journal of Medical Sciences)
Background: Metallo-β-lactamase (MBL) is becoming a bigger concern worldwide because of its ability to hydrolyze carbapenems which are the drug of choice for treating severe Gram-negative bacterial infections.